Update on Guidelines for the Management of Cancer‐Associated Thrombosis - Streiff, Michael B.; Abutalib, Syed Ali; Farge, Dominique; Murphy, Martina; Connors, Jean M.; Piazza, Gregory (The oncologist (Dayton, Ohio), 2021)
Cancer‐associated thrombosis (CAT) is a major cause of morbidity and mortality in patients with cancer. Over the past 2 decades, enormous advances have been made in the management of CAT. The growing evidence base informing practice has led to the publication of a number of guidelines and guidance documents on the diagnosis and treatment of CAT. The goal of this review is to examine the latest versions of evidence‐based guidelines, highlighting the differences and similarities in their methodology, their disease‐specific content, and recommendations for management. Our analysis shows that for most clinical topics, the different guidelines provide roughly similar management advice. However, there are a number of important clinical topics in CAT that are not currently covered by the existing guidelines. We think inclusion of these topics in future versions of the guidelines will facilitate ongoing efforts to optimize the care of patients with CAT. Implications for Practice Cancer‐associated thrombosis (CAT) is a common complication in patients with cancer. This review examines the differences and similarities of the current CAT guidelines methods and recommendations. Current guidelines largely agree on many aspects of CAT management. However, there are a number of topics in CAT that are not currently included in guidelines where evidence‐based guidance would be very helpful for clinicians. Coverage of these topics in future guidelines is encouraged to optimize clinical practice. Numerous guidelines for cancer‐associated thromboembolism have been published. This review compares recommendations from the most recent cancer‐specific guidelines, identifying areas in which guidance is lacking.